Die Verteilung der Primzahlen eines totalreellen algebraischen Zahlkörpers - Urbelis, J. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Урбялис. Распределение простых чисел чисто вещественного поля алгебраических чиселJ. Urbelis. Grynai realaus algebrinių skaičių kūno pirminių skaičių pasiskirstymas